PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS GENIALLY UNTUK MENINGKATKAN PEMAHAMAN SISWA DALAM PPKN KELAS IV SDN 2 PUTERAN - Nurhalifah, Silvi; Irfan Fajrul Falah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
There is a need for improvements in learning strategies, including the use of more interactive and varied learning media, in order to increase understanding so that Civics learning objectives can be achieved. By utilizing interactive media that is appropriate to Pancasila and Citizenship Education (PPKn) learning at the elementary school level, it will have a significant impact on the problem of students' low understanding of the material presented. Knowing the urgency to improve this condition, the author is encouraged to explore the use of genially based media as an innovative means to increase students' understanding of Civics learning subjects in class IV. The research method applied in this research is a quantitative approach with a pre-experimental type and using a one-group pre-test and post-test design. This research was conducted on fourth grade students and students at SDN 2 Puteran with a total of 25 students, 14 students and 11 female students. From the results of this research, it is proven that using genially based learning media can improve students' understanding as seen from the pretest and posttest results. The significance value is seen from 2-tailed < 0.05, which means the hypothesis is accepted, there is an influence on students' understanding of using learning media based on genially.